PRE-SCHOOL TEACHER PROFESSIONAL DEVELOPMENT: VALUE ASPECTS - Rutheniya R. Denisova (Высшее образование в России, 2016)
The article dwells on the problems of pre-school teacher's training in connection with the implementation of the important legal documents recently enacted in the system of pre-school education. The author analyzes the important professional qualities essential for a teacher, substantiates the demand for communicative and reflexive abilities of future teachers. Special attention is paid to the fact that the specialist training in the field of pre-school education should be carried out taking into account the uniqueness of pre-school age and the challenges facing the national education system.